Breast milk microRNAs: Potential players in oral tolerance development - Ahlberg, Emelie; Al-Kaabawi, Ahmed; Thune, Rebecka; Simpson, Melanie Rae; Pedersen, Sindre Andre; Cione, Erika; Jenmalm, Maria Christina; Tingö, Lina (Frontiers in Immunology, 2023)
Breast milk is an essential source of nutrition and hydration for the infant. In addition, this highly complex biological fluid contains numerous immunologically active factors such as microorganisms, immunoglobulins, cytokines and microRNAs (miRNAs). Here, we set out to predict the function of the top 10 expressed miRNAs in human breast milk, focusing on their relevance in oral tolerance development and allergy prevention in the infant. The top expressed miRNAs in human breast milk were identified on basis of previous peer-reviewed studies gathered from a recent systematic review (PROSPERO Identifier: CRD42020138989) and an updated literature search. The miRNAs with the highest expression levels in each study were used to identify the 10 most common miRNAs or miRNA families across studies and these were selected for subsequent target prediction. The predictions were performed using TargetScan in combination with the Database for Annotation, Visualization and Integrated Discovery. The ten top expressed miRNAs were: let-7-5p family, miR-148a-3p, miR-30-5p family, miR-200a-3p + miR-141-3p, miR-22-3p, miR-181-5p family, miR-146b-5p, miR-378a-3p, miR-29-3p family, miR-200b/c-3p and miR-429-3p. The target prediction identified 3,588 potential target genes and 127 Kyoto Encyclopedia of Genes and Genomes pathways; several connected to the immune system, including TGF-b and T cell receptor signaling and T-helper cell differentiation. This review highlights the role of breast milk miRNAs and their potential contribution to infant immune maturation. Indeed, breast milk miRNAs seem to be involved in several pathways that influence oral tolerance development.